Biopolymer Characterization: Gelatin from Poultry Waste as a Sustainable Alternative - Koneti, Priya B; Mohammad Raziuddin; Banerjee, Rituparna; Devangare, A A; Kulkarni, R C; Bhosale, Ashok V; Maheswarappa, Naveena B; Belore, Balaji; L, Judy; P, Sowmya; S, Thakre; M, Hangarkar (Journal of Meat Science, 2025)
The aim of this study was characterization of gelatin from chicken skin, head and feet blend by using two different food grade acids (Acetic acid and Citric acid). The extracted gelatins were analyzed for physico-chemical, proximate analysis, instrumental colour profile, textural profile analysis and determination of gel strength and viscosity. The gelatin treated with acetic acid has revealed higher protein percentage as well as gel clarity. No significant difference (P ≥ 0.05) in the yield was observed between the two groups. A significant increase (P ≤ 0.05) in pH and textural properties were observed in the gelatin treated with acetic acid. The hydroxyproline content, L* and b* values, gel strength and viscosity of acetic acid treated gelatin were significantly (P ≤ 0.05) lower as compared to citric acid treated one. Gelatin extracted from chicken skin, head and feet (SHF) blended with 3% acetic acid represents a potential alternative to the mammalian gelatin.